Slovenska mladinska realistična avanturistična proza - Haramija, Dragica (Otrok in knjiga, 1999)
The paper will present the perspective in genre in greater detail, that is the children's realistic adventurous prose, combining six sub-genres: naval adventurous prose, travellers' prose, sports adventurous prose, camping adventurous prose, detective stories and daily adventures. The most significant authors of such prose are: Tone Seliškar, Mirko Kunčič, Oskar Hudales, Anton Ingolič, Brane Dolinar, Leopold Suhodolčan, Vitan Mal, Ivo Zorman, Slavko Pregl, Ivan Sivec, Bogdan Novak, Dim Zupan, Primož Suhodolčan and Janja Vidmar. The children's adventurous prose shares the following characteristics: the main subject is the adventures, experienced and always successfully solved by main literary characters, most frequently by a group of children. The main hero a priori possesses positive characteristics and fights against a negative literary character (usually an adult). The story is usually set in the time of holidays, when children do not have any school obligations. The events follow each other synthetically. Most of the time the motivation is plausible, a story is narrated by a third-person narrator who handles the scenic perspective. Since hurrying and braking regularly replace each other, the atory unfolds at intervals. The most important element of such prose is an insoluble-soluble problem which turns out well. The prevailing events, people, a real literary place and time try to establish an image of a real, objective adventure
Keywords: mladinska književnost; young adult literature; avanturistična književnost; prose; proza; realistična proza